Supplemental Digital Learning Resource for Environmental Science: A Quasi-Experimental Study - Menrose J Bolalin (Journal of Basic Education Research, 2026)
Purpose of the study: This study aimed to develop and validate a supplemental digital learning resource in Environmental Science and to examine its classroom use as a support material for improving students’ understanding of selected competencies. Methodology: The study employed a quasi-experimental pretest-posttest design with control and experimental groups. A total of 174 senior high school students from four intact sections at a single school in the Bicol Region, Philippines, participated in the study. Two sections were assigned to the experimental group and two to the control group. The supplemental digital learning resource was developed using the ADDIE model and informed by elements of the 7E learning cycle in structuring learning activities. Prior achievement data were used to identify the least-mastered competencies, which served as the basis for the module's content. Data were analyzed using the weighted mean and the paired t-test. Main Findings: The developed supplemental digital learning resource obtained an overall weighted mean of 4.80, interpreted as Very Much Valid. Results also showed that both the control and experimental groups significantly improved from pretest to posttest. However, the experimental group obtained a higher posttest mean and a greater mean gain than the control group, suggesting that the supplemental digital learning resource may have provided additional instructional support for learning Environmental Science. Novelty/Originality of this study: The study contributes a competency-based supplemental digital learning resource in Environmental Science designed to address least-mastered competencies and support flexible and blended learning.